2008
DOI: 10.1016/j.neuron.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

D1 Receptors Physically Interact with N-Type Calcium Channels to Regulate Channel Distribution and Dendritic Calcium Entry

Abstract: Dopamine signaling through D1 receptors in the prefrontal cortex (PFC) plays a critical role in the maintenance of higher cognitive functions, such as working memory. At the cellular level, these functions are predicated to involve alterations in neuronal calcium levels. The dendrites of PFC neurons express D1 receptors and N-type calcium channels, yet little information exists regarding their coupling. Here, we show that D1 receptors potently inhibit N-type channels in dendrites of rat PFC neurons. Using coim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0
17

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 69 publications
(69 reference statements)
1
94
0
17
Order By: Relevance
“…Consistent with this idea, STDP rules can be altered by manipulating the shape and their back propagation of dendritic action potentials (40,41). Also, it is well known that dopamine can modulate calcium channels, potassium channels, and even calcium release from intracellular stores (31,(42)(43)(44). Indeed, it has been observed that dopamine increased the propagation of dendritic action potential in a subpopulation of hippocampal neurons (45).…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with this idea, STDP rules can be altered by manipulating the shape and their back propagation of dendritic action potentials (40,41). Also, it is well known that dopamine can modulate calcium channels, potassium channels, and even calcium release from intracellular stores (31,(42)(43)(44). Indeed, it has been observed that dopamine increased the propagation of dendritic action potential in a subpopulation of hippocampal neurons (45).…”
Section: Discussionmentioning
confidence: 93%
“…31,32 All of these mechanisms terminate G protein signaling and thus channel modulation, but in some cases, direct GPCR-Ca V 2 interactions have been demonstrated that result in endocytic removal of the channel from the plasma membrane upon GPCR desensitization. [33][34][35] Inhibition of Ca 2+ Channels by G Protein βγ…”
Section: G Protein Coupled Receptors and Heterotrimeric G Proteinsmentioning
confidence: 99%
“…183 D1 and D2 dopamine receptors also bind directly to Ca V 2.2 channels and modulate channel trafficking 33,184 and GABA B receptors also lead to channel internalization although the mechanism is somewhat different. 34 It is also worth noting that point mutations linked to familial hemiplegic migraine (FHM mutations) have been identified in Ca V 2.1 and lead to complex alterations in channel function.…”
Section: Modulation Of Gβγ-mediated Inhibition By Other Proteinsmentioning
confidence: 99%
“…One possibility is that presynaptic inhibition arises from reduction in the number of available signaling molecules at the plasma membrane of boutons. For example, agonist-induced cointernalization of Ca V 2.2 channel with GPCRs such as opioid-like-receptor ORL1 and dopamine D1 receptor have been observed in earlier studies (Altier et al, 2006;Altier and Zamponi, 2008;Kisilevsky et al, 2008). To test whether the membrane fraction of GB 1a Rs depends on activity-dependent concentration of GABA in the vicinity of boutons, we measured fluorescence of pHluorin, N-terminally tagged to the GB 1a protein as function of neuronal activity or agonist stimulation.…”
Section: Discussionmentioning
confidence: 96%